2022
DOI: 10.1002/adfm.202212299
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Sites Coordination Engineering of Single Atom Catalysts for Full‐Temperature Adaptive Flexible Ultralong‐Life Solid‐State Zn−Air Batteries

Abstract: High‐performance rechargeable Zn‐air batteries with long‐life stability are desirable for power applications in electric vehicles. The key component of the Zn‐air batteries is the bifunctional oxygen electrocatalyst, however, designing a bifunctional oxygen electrocatalyst with high intrinsic reversibility and durability is a challenge. Through density functional theory calculations, it is found that the catalytic activity originated from the electronic and geometric coordination structures synergistic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 50 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Raman spectrum of Cu‐Co/NC (Figure S12, Supporting Information) shows an I D / I G ratio of 1.28, confirming a more defective structure of the NC matrix, which facilitates the adsorption of oxygen intermediates during the ORR and OER reactions. [ 30 ] Moreover, the porous structure of Cu‐Co/NC was verified by N 2 adsorption/desorption measurements (Figure S13, Table S3, Supporting Information). The larger specific surface area and high porosity of Cu‐Co/NC are beneficial for promoting the exposure of metal sites and mass transfer during the reactions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Raman spectrum of Cu‐Co/NC (Figure S12, Supporting Information) shows an I D / I G ratio of 1.28, confirming a more defective structure of the NC matrix, which facilitates the adsorption of oxygen intermediates during the ORR and OER reactions. [ 30 ] Moreover, the porous structure of Cu‐Co/NC was verified by N 2 adsorption/desorption measurements (Figure S13, Table S3, Supporting Information). The larger specific surface area and high porosity of Cu‐Co/NC are beneficial for promoting the exposure of metal sites and mass transfer during the reactions.…”
Section: Resultsmentioning
confidence: 95%
“…[16,[25][26][27][28][29] Another effective approach is to construct SAs with two different transition metals through the synergetic effect of dual-metal sites to modulate the electrocatalysts' activity. [30][31][32][33][34][35][36][37][38] Such an approach takes advantage of the two isolated metal sites by pairing or long-range coupling to modulate the coordination and electronic structures, which correlates with the adsorption/desorption behavior of relevant oxygen intermediates. [39][40][41][42][43] However, a comprehensive study of the synergetic effect of isolated dual-metal sites has not been explored in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Fe 2p 3/2 and Ni 2p 3/2 characteristic peaks reveals the existence of Ni-N and Fe-N coordination. 45,46 The high-resolution N 1s spectrum is deconvoluted to four binding energy shis such as 398.8, 400.9, 402.5, and 405.1 eV, corresponding to pyridinic-N, pyrrolic-N, graphitic-N, and oxidized-N contents, respectively (Fig. 3d).…”
Section: Structure and Composition Analysismentioning
confidence: 99%
“…And their oxygen evolution reaction (OER) performance especially the long-run stability is also unsatisfactory. According to recent experimental/theoretical studies, rationally tailoring the central metal atom by introducing a secondary metal core (e.g., dual atom catalysts) and alternative coordination environment, such as ionic dopants, is an efficient approach to modulate the electronic configuration of the metal active sites to achieve suitable binding strength for oxygen-containing intermediates, thereby reducing the reaction energy barriers and boosting their catalytic activities. For example, Yang et al showed that the adjacent Mn–N moieties in Fe–N–C catalysts can cause Fe III electron delocalization and convert the spin state of Fe III from low to intermediate spin state, the latter of which can penetrate the antibonding π-orbital of oxygen, leading to enhanced ORR activity. , Tong et al developed a bimetallic single-atom catalyst consisting of CuN 4 and ZnN 4 sites. In this dual configuration, the low-electronegativity Zn atom donates an electron to Cu atoms and adjusts the d electron configuration of copper, ultimately benefiting the elongation and cleavage of O–O on the Cu active site and accelerating the ORR kinetics .…”
Section: Introductionmentioning
confidence: 99%